2019
DOI: 10.3847/1538-4357/aafbeb
|View full text |Cite
|
Sign up to set email alerts
|

Compton-thick AGNs in the NuSTAR Era. III. A Systematic Study of the Torus Covering Factor

Abstract: We present the analysis of a sample of 35 candidate Compton thick (CT-) active galactic nuclei (AGNs) selected in the nearby Universe (average redshift z ∼0.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 67 publications
15
44
0
Order By: Relevance
“…The distribution of AGN as a function of luminosity and absorbing column density is given by the XLF. Marchesi et al (2019) studied the torus covering factor of 35 Compton-thick objects using NuSTAR spectra, finding an average covering factor 0.5, i.e., θ OA 60 • . For the Swift-BAT 70-month AGN sample, Ricci et al (2017) found that for the 12 objects for which the opening angle of the torus could be constrained, the median value was similar, θ OA is 58 ± 3 • .…”
Section: Modeling Agn Spectramentioning
confidence: 99%
“…The distribution of AGN as a function of luminosity and absorbing column density is given by the XLF. Marchesi et al (2019) studied the torus covering factor of 35 Compton-thick objects using NuSTAR spectra, finding an average covering factor 0.5, i.e., θ OA 60 • . For the Swift-BAT 70-month AGN sample, Ricci et al (2017) found that for the 12 objects for which the opening angle of the torus could be constrained, the median value was similar, θ OA is 58 ± 3 • .…”
Section: Modeling Agn Spectramentioning
confidence: 99%
“…MYTorus, based on Monte Carlo simulations, self-consistently includes reflection and transmission (see e.g. Lanzuisi, et al 2015b for further details, Appendix B of Lanzuisi et al 2015a for a comparison with other models applied to heavily obscured AGN, and the recent work by Marchesi et al 2019). Additional components (low-energy scattering, host galaxy emission, and emission lines, as observed in particular in the X-ray spectrum of NGC1194) were included along with MYTorus.…”
Section: Spectral Modelingmentioning
confidence: 99%
“…In Marchesi et al (2018Marchesi et al ( , 2019, M18, M19 hereafter) we analyzed the combined 2-100 keV spectra of 35 candidate nearby (average redshift z =0.03) CT-AGN, i.e., all the 100-month BAT candidate CT-AGN having archival NuSTAR data. 2-10 keV data have been obtained using archival XMM-Newton, Chandra and Swift-XRT data.…”
Section: Introductionmentioning
confidence: 99%